The metaphor of border and the heuristics of borderline experiences and their significance for pedagogical thought and activity - Jaroslaw Gara (Studia z Teorii Wychowania)
The main thesis of this text is expressed in the statement that man is a “borderline being” – who lives within specific boundaries, and his adaptation and development are based on the dialectics of the borderline experience of various specific worlds and their regularities. A metaphor as such always possesses a certain “epistemological surplus” in the layer of its meanings, which may reveal the nature and specificity of that which is complex or ambiguous in its forms of existence. Therefore, the metaphor of border should be considered one of the most important clues in an attempt to bring human existence closer together. A border is something that separates, closes or opens a specific horizon of human experience. In this sense, reaching a border means approaching a particular end - where something can no longer have a simple continuation. Therefore, the objective existence of certain borders and their subjective impression give people an identity or induce them to commit acts of transgression (both constructive and destructive) that constitute an element of their ontological allocation in the surrounding material and natural, and socio-cultural worlds around them. Preserving or transcending specific borders is always experienced by man as something that brings both possibilities and threats to pedagogical impact and related human development.